Curriculum Innovation for the Internationalization of Islamic Education Study Program at Higher Education Institutions in Surabaya, Indonesia - Abd. Rachman Assegaf; Husniyatus Salamah Zainiyah; Muhammad Fahmi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2022)
Islamic Education Study Programs face various problems shaping curriculum innovation for an International Class Program (ICP). This research focused on efforts to innovate the appropriate curriculum for Islamic Education Study Programs at UIN Sunan Ampel Surabaya (UINSA), State University of Surabaya (UNESA), and the Sepuluh Nopember Institute of Technology (ITS) in Surabaya, Indonesia. The research method carried out in this study is developmental research using a qualitative approach and comparative analysis. Data were collected through visits, interviews, and direct observation with full awareness of health protocols, as well as documentation from printed and electronic materials. In addition, data were collected through Focus Group Discussions (FGD) and the Delphi Method, a smaller scale of FGD. The results show that Islamic Education Study Program needs to immediately establish an international class program starting from the takhassus class, the excellent class, and the international class. Based on the findings at UNESA and ITS, the patterns of international classes are different in terms of programs, curriculum, learning, and multimedia application, which makes the position of the Islamic Education Study Program more flexible.